2015
DOI: 10.1016/j.ejso.2015.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of inflammation-based prognostic score on survival after curative thoracoscopic esophagectomy for esophageal cancer

Abstract: The present study demonstrated that GPS is associated with prognosis and can be considered as an independent prognostic marker in patients who underwent esophagectomy. Moreover, the GPS has the advantage of being simple to measure, routinely available and well standardized. But the present study failed to confirm the NLR as a significant predictor of survival following resection for esophageal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
4

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 31 publications
2
35
4
Order By: Relevance
“…In contrast, several studies did not show PLR and NLR to be independent prognostic factors [3638]. In the present study, although PLR, NLR, and GPS were found to be predictive factors for OS and RFS on univariate analyses, multivariate analysis did not show these markers to be independent prognostic factors.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, several studies did not show PLR and NLR to be independent prognostic factors [3638]. In the present study, although PLR, NLR, and GPS were found to be predictive factors for OS and RFS on univariate analyses, multivariate analysis did not show these markers to be independent prognostic factors.…”
Section: Discussioncontrasting
confidence: 99%
“…Tumor stage III, high NLR and low PNI were identified to be poor DFS and OS factors in patients with operable thoracic ESCCs. These findings have been reported previously (25)(26)(27). Specifically, it our study has revealed, via the multivariable analysis of our present cohort, that NLR was an important prognostic marker in patients with thoracic ESCCs independent of the tumor stage.…”
Section: Discussionsupporting
confidence: 92%
“…Accumulating evidence suggests that host immune responses are important prognostic indicators, and several inflammation-based postoperative prognostic scoring systems have been described 15. Cancer-related inflammation suppresses antitumor immunity through the recruitment of regulatory T cells and the activation of chemokines that result in tumor progression and metastasis 16…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, a number of studies have confirmed the clinical utility of systemic inflammation-based prognostic scores for predicting postoperative survival in patients with various types of solid tumors 1517. Although the LMR, NLR, and PLR can predict the prognosis of patients with various types of cancer, their prognostic value and the optimal cutoff points in patients with esophageal cancer remain to be determined 7,10,18.…”
Section: Discussionmentioning
confidence: 99%